ANALYSIS OF THE CAUSES OF HYPERTENSION IN PREGNANCY: IN THE PONEK ROOM OF DR WAHIDIN SUDIRO HUSODO REGIONALHOSPITAL, MOJOKERTO CITY - Indah Kusmindarti; Nila Triayuningsasi (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
The maternal mortality rate (MMR) in Indonesia is still relatively high, reaching 183 per 100,000 live births based on the national target of the 2024 National Medium-Term Development Plan (RPJMN). With 4,150 cases, this figure shows a significant gap from the target set in the 2024 RPJMN. The three main causes of maternal death in Indonesia are gestational hypertension (GHD), hemorrhage, and infection. These three causes are largely preventable with appropriate and prompt medical intervention. Despite improvements in the quality of prenatal care, the incidence of gestational hypertension continues to rise. The exact cause of gestational hypertension remains unknown, and the disease is thought to be multifactorial. Currently, there is no definitive way to prevent gestational hypertension . Research Objective: This study was conducted to evaluate the factors causing hypertension in pregnancy and to provide appropriate preventive solutions. The research method used was descriptive research with an observational approach to examine the characteristics of patients with hypertension in pregnancy at Dr. Wahidin Sudiro Husodo Regional General Hospital, Mojokerto City, in 2024-2025. Based on the results of the research that has been carried out, the analysis results obtained by the Maternal Age variable have a p-value of 0.877 (> 0.05), so it can be concluded that there is no relationship between Maternal Age and the occurrence of Hypertension in Pregnancy, the Parity variable has a p-value of 0.995 (> 0.05), so it can be concluded that there is no relationship between Parity and the occurrence of Hypertension in Pregnancy, the Gestational Age variable has a p-value of 0.998 (> 0.05), so it can be concluded that there is no relationship between Gestational Age and the occurrence of Hypertension in Pregnancy, the Obesity variable has a p-value of 0.998 (> 0.05), so it can be concluded that there is no relationship between Obesity and the occurrence of Hypertension in Pregnancy, the Gestational DM variable has a p-value of 0.988 (> 0.05), so it can be concluded that there is no relationship between Gestational DM and the occurrence of Hypertension in Pregnancy.